Rechargeable batteries: Technological advancement, challenges, current and emerging applications. (1st March 2023) - Olabi, Abdul Ghani; Abbas, Qaisar; Shinde, Pragati A.; Abdelkareem, Mohammad Ali
Abstract: Historically, technological advancements in rechargeable batteries have been accomplished through discoveries followed by development cycles and eventually through commercialisation. These scientific improvements have mainly been combination of unanticipated discoveries and experimental trial and error activities. However, with the increased complexity of rechargeable battery systems and diversification in ever-demanding new applications requires a strategical approaches to commercialise newly developed battery chemistries. This can only be achieved by fast-tracking the transfer of key finding from scientific laboratories to industrial collaborators in order to design commercially feasible devices. Despite the dominance of lithium-ion batteries (LiBs) commercially in current rechargeable battery market which ranges from small scale applications such as portable electronic devices to large scale applications including transportation to grid scale electrical energy storage. Scientific community is endeavouring to consolidate the global rechargeable battery portfolio with the alternative rechargeable battery systems based on cost-effective, safe, and environmentally friendly battery chemistries. This brief prospective will provide an update on the historical developments, current technological scenario and future expectations, current and potential applications, and challenges faced by current and future rechargeable battery technology. Highlights: Brief overview working principle of different rechargeable battery systems. Technological progression of rechargeable battery technology. Challenges face by current battery technology. Current and emerging applications of rechargeable batteries.